Hadith #3795 - Sunan Abi Dawud - Abdur Rahman bin Shabal al-Ansari; Abu Rashid al-Hbrany أبو راشد الحبراني; al-Hakm bin Nafi', Abu al-Yaman الحكم بن نافع أبو اليمان الحمصي; Damdam bin Zar'ah ضمضم بن زرعة بن ثوب; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
We were in an army with the Messenger of Allah (ﷺ). We got some lizards. I roasted one lizard and brought it to the Messenger of Allah (ﷺ) and placed it before him. He took a stick and counted its fingers. He then said: A group from the children of Isra’il was transformed into an animal of the land, and I do not know which animal it was. He did not eat it nor did he forbid (its eating).
Grade: Sahih

Hadith #4070 - Sunan Abi Dawud - Damdam bin Zar'ah ضمضم بن زرعة بن ثوب; Habib bin 'Ubaid al-Rhby حبيب بن عبيد الرحبي; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
We went out with the Messenger of Allah (ﷺ) on a journey, and we had on our saddles and camels garments consisting of red warp of wool. The Messenger of Allah (ﷺ) said: Do I not see that red colour has dominated you. We then got up quickly on account of this saying of the Messenger of Allah (ﷺ) and some of our camels ran away. We then took the garments and withdrew them.
Grade: Da'if

Hadith #4887 - Sunan Abi Dawud - Abu Umama bin Sahl; Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; Damdam bin Zar'ah ضمضم بن زرعة بن ثوب; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Jubayr bin Nufayr al-Hadrami; Kathir bin Marrah al-Hadrami كثير بن مرة الحضرمي; Sa'id bin 'Amr bin Sa'id bin al-Aas سعيد بن عمرو بن سعيد بن العاص; Sharyh bin 'Ubaid شريح بن عبيد بن شريح (Sunan Abi Dawud)
Is one of you unable to be like Abu Damdam? The people asked: who is Abu Damdam? He replied : A man of old before you. He then mentioned the rest of tradition to the tradition to the same effect. This version has : who would say (in the morning) : My honors is for the one who reviles me. Abu Dawud said: This tradition has also been transmitted by Hashim bin al-Qasim from Muhammad b. ‘Adb Allah al-‘Ammi from Thabit on the authority of Anas from Prophet (ﷺ) to the same effect. Abu Dawud said
Grade: Da'if